The Improving Students’ Scientific Reasoning through Discovery Learning in Elementary Science Instruction - Helmia Tasti Adri; Suwarjono Suwarjono (CV. Edujavare Publishing, 2024)
Scientific reasoning is an essential competency in elementary science education, yet many students show limited ability to analyze evidence, formulate hypotheses, and draw logical conclusions due to teacher-centered instruction. This classroom action research aimed to improve students’ scientific reasoning through the implementation of the Discovery Learning model. The study involved 28 fourth-grade students at SD Amaliah and was conducted in three cycles consisting of planning, action, observation, and reflection. Data were collected through scientific reasoning tests, observations, and field notes, then analyzed descriptively. The results showed a significant improvement in students’ scientific reasoning, with average scores increasing from 56.8 in the pre-action stage to 87.4 in Cycle III, while learning mastery improved from 36% to 92%. These findings indicate that Discovery Learning effectively enhances scientific reasoning by encouraging active inquiry and evidence-based problem-solving. It can be concluded that Discovery Learning is an effective instructional model for elementary science learning.